A NATIONWIDE ANALYSIS OF LITIGATION IN NEUROLOGICAL PRACTICE. Issue 10 (9th September 2014) - Coysh, Thomas; Breen, David
Abstract : Objectives: We set out to study the nature of successful litigation claims in order to inform neurologists and neurosurgeons about hazardous areas within their specialties and potentially alter clinical practice. Design: Nationwide retrospective analysis of successful neurology and neurosurgery claims over a 17-year period. Setting: We studied all successful claims occurring between 1995 and 2012 using the NHS Litigation Authority database, which collects data on claims made against clinicians practicing in England and Wales. Participants: 423 successful claims were identified during the study period. Main outcome measures: The errors involved, the patient groups affected, the resulting mortality and the litigation payments. Results: Missed diagnosis was the most common cause of litigation, followed by negligent performance of a procedure. Cerebrovascular disease and intracranial tumours were the most frequently missed diagnoses. Litigation payments were significantly higher in neurosurgery compared to neurology cases. Conclusions: This is the first study of successful litigation claims against the NHS for negligent neurological or neurosurgical care and provides data to help reduce risk and improve patient safety.